PENGARUH PROGRESSIVE MUSCLE RELAXATION TERHADAP TINGKAT KECEMASAN PRE OPERASI DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2018 - Barus, Mardiati; Simanullang, Murni Sari Dewi; Gea, Erni Cahyani Putri (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Operation  is  in  one  of  the  medical  action  that  needs  mental  and physical preparation. Medical action could cause physiology interference that is worries. Base on preliminary data, there are many patient get big worries before operation  does.  One  of  the  interventions  to  reduce  worries  pre  operation  is progressive muscle relaxation.This research is aim to identify the different rates worry level before and after doing the progressive muscle relaxation to the patient pre operation in Santa Elisabeth Hospital Medan 2018.The research design is using Quasy Experimental by One Group PreTest Post Test without Control Group Design.The result of this research is about pre test 14,33 and post test 12,40 the significancy  value  p  value  =  0,000  that  state  there  is  correlation  between progressive muscle relaxation to worries level in pre operation in Santa Elisabeth hospital 2018. The  conclusion  of  this  progressive  muscle  relaxation  research  is there  is  correlation  between  reduce  worry  to  pre  patient  operation.  Nurse  is expected  to  do  progressive  muscle  relaxation  as  one  of  intervention  nursing  to reduce worry to pre operation patient.